Echoes of Italy nova et antiqua in the chilean letters (Iter, 2022)
“ Echoes of Italy in the chileanletters ” intends to check the presence ofilatian writers or some of theirdescendants, as well as the influences of some aspects of the italianletters in chilean literary history. To that end, national works are revised,starting with La Araucana up to the current narrative and poetry,specially the one that ineludes somefeatures takenfrom the great ancientRomán authors or outstanding italian writers. Finally, a summary oftheliterary activity of italian authors who Uve in Chile or their descendantsis submmitted to the readers.